Removal of As(iii) from water using modified jute fibres as a hybrid adsorbent1. Issue 14 (19th February 2015) - Hao, Linlin; Zheng, Tong; Jiang, Jiping; Hu, Qi; Li, Xilan; Wang, Peng
<x xml:space="preserve">Abstract</x> Jute fibres were modified to produce an effective hybrid adsorbent with the advantages of an excellent arsenic removal effect and easy retrieval from rivers or lakes.